DEVELOPMENT OF POL YPHENYLENE OXIDE-SILICOALUMINOPHOSPHATE MIXED MATRIX MEMBRANES FOR GAS SEPARATION - GEBRETSADIK, BIRUH SHIMEKIT (2012)
This present research has developed new flat sheet dense mixed matrix membranes (MMM) that were comprised of poly (2,6-dimethyl-1,4-phenyleneoxide) (PPO) as polymer matrix and three different silicoaluminophosphates (SAPO) namely pure SAPO, sodium glycinate drived SAPO (GlyNa-SAPO) and aminopropyl triethoxysilane modified SAPO (APTES-SAPO) as molecular sieves via the solution casting method. Morphological analysises have shown that the newly developed MMMs provide evidence for good interfacial contact between the PPO polymer and the particles (SAPO, GlyNa-SAPO and APTES-SAPO) loadings at 2 wt.% and 5 wt.%. It was also found out that the introduction of the aforementioned molecular sieves into the PPO matrix improved the thermal stability of the newly developed MMMs over the PPO homogenous membrane. The differential scanning calorimetry (DSC) results showed that when the loadings of the (SAPO, GlyNa-SAPO and APTES-SAPO) molecular sieves increased from 2 wt.% to 10 wt.%, the glass transition temperature (T g) of MMMs also increased from 223.29°C to 225.83°C indicating the presence of rigidification effect. It was also found out that the annealing treatment has improved the thermal stability (thermal degradation temperature) and the Tg of the newly developed MMMs over unannealed membranes. The Fourier transform infrared (FTIR) analysis has also showed that the introduction of the SAPO, GlyNa-SAPO and APTES-SAPO functional groups and their specific interactions present in the PPO matrix. The gas permeation studies of the newly developed MMMs (SAPO-PPO, GlyNa-SAPO-PPO and APTES-SAPO-PPO) showed better gas separation performance in terms of ideal selectivity (C02/CH4 and C02/N2) over the homogenous PPO membranes. However, it was found that the addition of2 wt% to 10 wt% loading of the SAPO, GlyNa-SAPO and APTES-SAPO molecular sieves decreased the permeance of the tested gases over the PPO homogenous membrane. Within a pressure range of (2-1 0) bar, the permeation of C02 across the MMMs increased in the order of APTES-SAPO-PPO MMMs followed by GlyNa-SAPO-PPOMMMs and SAPO-PPO MMMs, respectively. However, the permeation slightly decreased in the order APTES-SAPO-PPO MMMs followed by GlyNa-SAPO-PPO MMMs and SAPO-PPO MMMs for N2 and CH4 gases, respectively. From the newly developed twelve MMMs, the best ideal selectivity of target gases was found in APTES-SAPO-PPO MMMs at 10 wt.% loadings and 10 bar as much as 23.90 and 5.65 for the respective gas pairs of C02/CH4 and COz/Nz system. It was also found out that the annealing treatment at temperature of 235 °C reduced the permeance of target gases but improved the ideal selectivity of target gases (COz/CH4 and COz/Nz) of the developed MMMs compared with PPO homogenous membrane. The highest ideal selectivity achieved was found in annealed APTES-SAPO-PPO MMMs at 10 wt.% loadings and 10 bar with the values of 26.89 and 7.54 for the respective gas pairs of COz/CH4 and COz/Nz system, respectively. A modified Pal model which is developed in this work by taking into account of the presence of the interfacial rigidified matrix chain effect has been able to predict well the permeability and selectivity of these new MMMs. The permeation data of the newly fabricated poly (2,6-dimethyl-1 ,4-phenylene oxide )-SAPO MMMs were used for further validation of the newly developed model. Based on the computation, AARE % was found less than I%. Hence, the present developed model proved that the permeability and the selectivity of gases through non-ideal MMMs, could be predicted accurately.